Complience with school-based social distancing practices among teachers and head teachers during coronavirus disease 2019 pandemic in vocational enterprises institutes in abuja, Nigeria - Arah, A. S; Abdulhamid, U.; Adamu, D; Musa, Y. S (Research Parks Publishing LLC, 2021)
The study ascertained the level of compliance with school-based social distancing practices among teachers and head teachers during COVID-19 pandemic in Vocational Enterprises Institute in Abuja, Nigeria. Two research questions were raised to guide the study and one hypothesis was formulated and tested at .5 level of significant. The research design used for this study was the descriptive survey research design, specifically, using cross-sectional study. The population of the study was 154 respondents consisting of 91 male and 63 female teachers. Total population sampling technique was used to select the whole population of the study. The instrument used for data collection was compliance with School-Based Social Distancing Practices Scale (S-BSDPS). The reliability indices of the instrument were found to be .88 and .91 using Cronbach Alpha statistical method. The study employed the use of mean to answer the research questions and Analysis of Variance (ANOVA) to test the null hypothesis using Statistical Package for Social Sciences (SPSS) version 25. Findings revealed that, teachers complied with 6 items and failed to comply with1 item while head teachers complied with 7 and failed to comply with 5 items on the school-based social distancing practices scale. The study recommended that, the education secretariat of the Federal Capital Territory, Abuja should enforce the full compliance with school-based social distancing practices among head teachers during COVID-19 pandemic